Coherent photonic-phononic interactions in integrated circuits - Stiller, Birgit; Merklein, Moritz; Eggleton, Benjamin J. (23rd Opto-Electronics and Communications Conference, OECC 2018, 2018)
Using stimulated Brillouin scattering, we experimentally demonstrate a coherent storage concept that is suitable for multiple optical wavelengths and storage of 200ps-long optical pulses for over 70 pulse widths.
CRIS-Team Scopus Importer:2021-06-29